![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x-1\right)^3=27\)
\(\Leftrightarrow\left(x-1\right)^3=3^3\)
\(\Leftrightarrow x-1=3\)
\(\Leftrightarrow x=4\)
\(x^2+x=0\)
\(\Leftrightarrow x\left(x+1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x=-1\end{cases}}\)
Vậy x = 0 hoặc x = -1
\(\left(2x+1\right)^2=25\)
\(\Leftrightarrow\left(2x+1\right)^2=\left(\pm5\right)^2\)
\(\Leftrightarrow\orbr{\begin{cases}2x+1=5\\2x+1=-5\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2\\x=-3\end{cases}}\)
Vậy x = 2 hoặc x = -3
\(\left(2x-3\right)^2=36\)
\(\Leftrightarrow\left(2x-3\right)^2=\left(\pm6\right)^2\)
\(\Leftrightarrow\orbr{\begin{cases}2x-3=6\\2x-3=-6\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=4,5\\x=-1,5\end{cases}}\)
Vậy x = 4,5 hoặc x = -1,5
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\frac{1}{81}\right)^x\cdot27^{2x}=\left(-9\right)^4\)
\(\frac{1}{81^x}\cdot\left(3^3\right)^{2x}=9^4\)
\(\frac{3^{6x}}{3^{4x}}=3^8\)
\(3^{2x}=3^8\)
\(\Leftrightarrow2x=8\)
\(\Leftrightarrow x=4\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ Ta có: 27x : 3x = 9
=> 33x-x = 9 =\(\left(\pm3\right)^2\)
=> 3x - x = 2
=> 2x = 2
=> x = 1
Vậy x = 1
b/ Ta có:
1/2 . 2x + 4 . 2x = 9 . 25
=> 2x . ( 1/2 + 4 ) = 9 . 32
=> 2x . 9/2 = 288
=> 2x = 64
=> x = 32
Vậy x = 32
a ) 27x : 3x = 9
<=> ( 27 : 3 )x = 9
<=> 9x = 9
=> x = 1
b )\(\frac{1}{2}.2x+4.2x=9.2^5\)
<=> x + 8x = 9.32
<=> 9x = 288
=> x = 288 : 9 = 32
![](https://rs.olm.vn/images/avt/0.png?1311)
1: Tìm x
a) Ta có: \(\left(2x-1\right)^3=-27\)
\(\Leftrightarrow2x-1=-3\)
\(\Leftrightarrow2x=-3+1=-2\)
hay x=-1
Vậy: x=-1
b) Ta có: \(\left(2x-3\right)^4=625\)
\(\Leftrightarrow\left[{}\begin{matrix}2x-3=-5\\2x-3=5\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=-5+3=-2\\2x=5+3=8\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-1\\x=4\end{matrix}\right.\)
Vậy: \(x\in\left\{-1;4\right\}\)
c) Ta có: \(\left(x-2\right)^5=\left(x-2\right)^7\)
\(\Leftrightarrow\left(x-2\right)^5-\left(x-2\right)^7=0\)
\(\Leftrightarrow\left(x-2\right)^5\left[1-\left(x-2\right)^2\right]=0\)
\(\Leftrightarrow\left(x-2\right)^5\cdot\left[1-\left(x-2\right)\right]\cdot\left[1+\left(x-2\right)\right]=0\)
\(\Leftrightarrow\left(x-2\right)^5\cdot\left(1-x+2\right)\cdot\left(1+x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)^5\cdot\left(-x+3\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}\left(x-2\right)^5=0\\-x+3=0\\x-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x-2=0\\-x=-3\\x=1\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=2\\x=3\\x=1\end{matrix}\right.\)
Vậy: \(x\in\left\{1;2;3\right\}\)
d) Ta có: \(5^{x+2}+5^{x+3}=750\)
\(\Leftrightarrow5^{x+2}\cdot1+5^{x+2}\cdot5=750\)
\(\Leftrightarrow5^{x+2}\left(1+5\right)=750\)
\(\Leftrightarrow5^{x+2}\cdot6=750\)
\(\Leftrightarrow5^{x+2}=125\)
\(\Leftrightarrow x+2=3\)
hay x=1
Vậy: x=1
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)
\((3x-7)^5=0\Rightarrow 3x-7=0\Rightarrow x=\frac{7}{3}\)
b)
\(\frac{1}{4}-(2x-1)^2=0\)
\(\Leftrightarrow (2x-1)^2=\frac{1}{4}=(\frac{1}{2})^2=(-\frac{1}{2})^2\)
\(\Rightarrow \left[\begin{matrix} 2x-1=\frac{1}{2}\\ 2x-1=\frac{-1}{2}\end{matrix}\right.\Rightarrow \Rightarrow \left[\begin{matrix} x=\frac{3}{4}\\ x=\frac{1}{4}\end{matrix}\right.\)
c)
\(\frac{1}{16}-(5-x)^3=\frac{31}{64}\)
\(\Leftrightarrow (5-x)^3=\frac{1}{16}-\frac{31}{64}=\frac{-27}{64}=(\frac{-3}{4})^3\)
\(\Leftrightarrow 5-x=\frac{-3}{4}\)
\(\Leftrightarrow x=\frac{23}{4}\)
d)
\(2x=(3,8)^3:(-3,8)^2=(3,8)^3:(3,8)^2=3,8\)
\(\Rightarrow x=3,8:2=1,9\)
e)
\((\frac{27}{64})^9.x=(\frac{-3}{4})^{32}\)
\(\Leftrightarrow [(\frac{3}{4})^3]^9.x=(\frac{3}{4})^{32}\)
\(\Leftrightarrow (\frac{3}{4})^{27}.x=(\frac{3}{4})^{32}\)
\(\Leftrightarrow x=(\frac{3}{4})^{32}:(\frac{3}{4})^{27}=(\frac{3}{4})^5\)
f)
\(5^{(x+5)(x^2-4)}=1\)
\(\Leftrightarrow (x+5)(x^2-4)=0\)
\(\Leftrightarrow \left[\begin{matrix} x+5=0\\ x^2-4=0\end{matrix}\right.\Leftrightarrow \left[\begin{matrix} x+5=0\\ x^2=4=2^2=(-2)^2\end{matrix}\right.\)
\(\Rightarrow \left[\begin{matrix} x=-5\\ x=\pm 2\end{matrix}\right.\)
g)
\((x-2,5)^2=\frac{4}{9}=(\frac{2}{3})^2=(\frac{-2}{3})^2\)
\(\Rightarrow \left[\begin{matrix} x-2,5=\frac{2}{3}\\ x-2,5=\frac{-2}{3}\end{matrix}\right.\Rightarrow \left[\begin{matrix} x=\frac{19}{6}\\ x=\frac{11}{6}\end{matrix}\right.\)
h)
\((2x+\frac{1}{3})^3=\frac{8}{27}=(\frac{2}{3})^3\)
\(\Rightarrow 2x+\frac{1}{3}=\frac{2}{3}\Rightarrow x=\frac{1}{6}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
nhé
a)(2x-1)6=(2x-1)8
=> (2x-1)8-(2x-1)6=0
=> (2x-1)6.((2x-1)2-1)=0
+)th1(2x-1)6=0
+)th2((2x-1)2-1)=0
a) \(\left(2x-1\right)^6=\left(2x-1\right)^8\)
\(\Rightarrow\left(2x-1\right)\in\left\{\pm1;0\right\}\)
TH1 : \(2x-1=0\) TH2 : \(2x-1=-1\) TH3 : \(2x-1=1\)
\(2x=1\) \(2x=0\) \(2x=2\)
\(x=\frac{1}{2}\) \(x=0\) \(x=1\)
Vậy \(x\in\left\{\frac{1}{2};0;1\right\}\)
b) Tương tự